Anti-Metastatic Effect of Boiled Garlic Extract on A549 Lung Cancer Cells Line by FAK Mechanism - Munawir, AL (Jurnal Kedokteran Brawijaya, 2015)
According to epidemiological and animal study, the daily intake of garlic have important role in decreasing of cancer prevalence and tumor metastasis. However, mechanism of anti-metastatic of garlic is not fully understood. In the present study, we examined the anti metastatic effect of a brief exposure to boiled garlic extract (BGE) on A549 Lung cancer cells. Cytotoxicity BGE on A549 lung cancer cells was tested using MTT Assay. Migration and invasion scratching wound assay A549 lung cancer cells was tested usingscratching wound assay and agarose dropt explants assay.The growth of A549 lung cancer cell was measured using Colony forming assay. To explore the molecular mechanism and effect of BGE on migration and invasion, western blotting was used to analyze the FAK/Paxillin pathway. We found that BGE inhibits the growth, migration and invasion of A549 lung cancer cells at 300 µg/mL. Interestingly, BGE inhibits migration and invasion of A549lung cancer cells by decreasing the total of FAK and P-Y397 expression at 6 hours after a brief exposure, but not influence of the paxillin expression. We think the present finding demonstrate a novel anti-metastatic effect of garlic and suggests a certain garlic-derived compounds, BGE may be potential agent for inhibiting migration and invasion through decreasing the total of FAK and P-Y397 expression in the cancer cell. Keywords: A549 lung cancer cells, boiled garlic extract, FAK mechanism, migration cell